The use of functional loads to improve sports performance of football players (Experimental biology, 2015)
This paper presents the results of players to explore the use of functional loads. The proposed system of training players in the weekly cycle with a change in the intensity and form of executable load exercises allowing for improved athletic performance coupled with a high level of functional state of the major functional systems of the body, cardio-vascular. The results obtained can be used to study the construction of the training process for the preparation of professional athletes, for athletes and enthusiasts.
Keywords: functional loads; system physical training; sports performance of football players